Effect of corporate governance on real activity-based earnings management: evidence from Korea - Kang, Sun-A; Kim, Yong-Shik (Journal of Business Economics and Management, 2012)
This paper aims to determine whether corporate governance affects manager's real operating or investment decision to control reported earnings. Through data analysis of firms listed on the Korean stock exchange, it was found that the aggregated measure of real activity-based earnings management decreases as the size of board is larger or as a greater proportion of external directors sit on the board. Those findings are almost the same, whether a corporate governance index composed by each BOD characteristics is employed, or problem caused by endogenous relationships among variables is controlled. The results provide the first empirical evidence that real activity-based earnings management is influenced by corporate governance structure. This focus on real activity-based earnings management suggests new avenues for research on corporate governance. The results offer some insights for policy makers interested in promoting legislation to ensure strong corporate governance in their nation.Article in English.Įmonių valdymo poveikis, pagrįstas darbo užmokesčio valdymu: Korėjos pavyzdysSantrauka. Šiame straipsnyje siekiama nustatyti, kokią įtaką turi kompanijos vadovo sprendimai, susiję su gaunamų pajamų iš darbuotojų tiesioginės veiklos / operacijų ar investicinių sprendimų kontrole. Tyrime dalyvavo Korėjos kompanijos. Autorių atlikti tyrimai parodė, kad darbuotojų darbo užmokesčio valdymas yra efektyvesnis nei tiesioginė vadovo kontrolė. Straipsnyje minima, kad priėmus sprendimą valdyti darbo užmokesčius, būtina keisti visą įmonės valdymo struktūrą. Gauti rezultatai yra kaip siūlymas peržiūrėti atitinkamus nacionalinius teisės aktus Korėjoje.Reikšminiai žodžiai: įmonių valdymas, darbo užmokestis, valdymas, pajamos, kompanijos